The impact of male factor infertility on early and late morphokinetic parameters: a retrospective analysis of 4126 time-lapse monitored embryos. Issue 1 (21st January 2020) - Sacha, C R; Dimitriadis, I; Christou, G; James, K; Brock, M L; Rice, S T; Bhowmick, P; Bormann, C L; Souter, I
Abstract: STUDY QUESTION: Is there an effect of male factor infertility (MFI) on either early or late morphokinetic parameters obtained during embryonic culture to blastocyst stage in a time-lapse imaging (TLI) incubator? SUMMARY ANSWER: Neither mild nor severe MFI had an impact on overall time to blastocyst or duration of individual cleavage stages in the total embryo population. WHAT IS KNOWN ALREADY: Prior studies have suggested that paternal DNA and sperm quality affect embryo morphokinetic parameters, but the impact of MFI is not fully understood. STUDY DESIGN, SIZE, DURATION: This retrospective cohort study, at a major academic fertility centre, included 536 couples (women, ≤44 years of age) undergoing IVF between September 2013 and September 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data from 4126 embryos cultured to the blastocyst stage in a TLI-monitored incubator were retrospectively reviewed. Embryos derived from the sperm of men with MFI were compared with those derived from patients with other infertility diagnoses. Generalized fixed and random effects models, t -test and χ 2 were used as appropriate. MAIN RESULTS AND THE ROLE OF CHANCE: Couples with MFI had a higher rate of ICSI utilization and fewer usable embryos on average, and the men were older compared with couples with other diagnoses. Additionally, the women in MFI couples were younger and had higher antral follicle counts (AFCs) and higher anti-Müllerian hormone (AMH) levels compared with the other women undergoing IVF. When controlling for maternal and paternal ages, AMH and fertilization method (conventional IVF versus ICSI), neither mild nor severe MFI affected duration of individual cleavage stages or overall time to the blastocyst stage, when all or only usable embryos were examined (coefficient 0.44 hours in all embryos, P = 0.57; coefficient 0.39 hours in usable embryos, P = 0.60). Whether the sperm was surgically extracted similarly had no significant effect on embryo morphokinetic parameters. When the fertilization method was assessed independently, ICSI lengthened the overall time to blastocyst stage by 1.66 hours ( P = 0.03) on average, primarily due to an increase in duration of the time from 5-cell embryo stage to early blastulation (P5SB). LIMITATIONS, REASONS FOR CAUTION: This large cohort study avoided embryo selection bias due to random assignment of embryos to the TLI incubators. However, our findings may not be generalizable to groups under-represented in our clinic population. Future studies should also evaluate the impact of male hormonal status and detailed sperm morphology, such as head versus flagellum defects, on embryo morphokinetic development. WIDER IMPLICATIONS OF THE FINDINGS: Our findings suggest that the fertilization method rather than MFI per se impacts time to early blastulation. The clinical implications of this effect on embryo development warrant further investigation. STUDY FUNDING/COMPETING INTEREST(S): There were no sources of funding for this study. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A